If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4x + -6(-2 + 4) = 64 Combine like terms: -2 + 4 = 2 -4x + -6(2) = 64 Multiply -6 * 2 -4x + -12 = 64 Reorder the terms: -12 + -4x = 64 Solving -12 + -4x = 64 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + -4x = 64 + 12 Combine like terms: -12 + 12 = 0 0 + -4x = 64 + 12 -4x = 64 + 12 Combine like terms: 64 + 12 = 76 -4x = 76 Divide each side by '-4'. x = -19 Simplifying x = -19
| 2x+y-z=7z | | -4x-6(-2+4)=64 | | 3x-1=-3x+3 | | 3x-1=-3x+3 | | -5x+-2=-2X+4 | | -6x-5(-3x-3)=60 | | 114=2x+3x | | 5x+7y=3890 | | 8x+7y-5-5x+6y-3= | | -2x-2(-5x-4)=-80 | | 15+4y-1=15y-13-2y | | y+(y-2)2=2 | | 3x-n=7+n | | 25-13=3(x-1) | | -13.9=b+17.1 | | r+7= | | 15-44=3(x-4)-5 | | 3x+(x-5)=15+4 | | -16+13=m-2 | | -3x=8-(-1) | | 3w+5-2w+7= | | 2x^6=-3 | | 5mn-2m(m-2n)= | | 7(x+2)-3x=4(x-1)+10 | | -13.9=b-17.1 | | 3(2n-m)+4m= | | -9x+7=16 | | 9X-2(8-X)=61 | | f(x+2)=9x-1 | | -(6-y+3)-(-5y-8)=2 | | e+73=7 | | =2x^2-36x |